Avaliação de algumas propriedades físicas de grãos de café (Coffea arabica) orgânico e convencional - Dias, Luciani Fatima Lopes (2007)
The coffee is one of the main item of exportation together, with the sugar and the cotton. Organic agriculture became a market in expansion, with great perspectives for the producer. The organic coffee is a differentiated product, of bigger added value, whose market has grown and if fortified throughout the years. Although the coffee to be an old culture, studies on its physical properties are limited and dispersed. The knowledge of the physical characteristics of the products harvested in Brazil is essential for the project, construction and operation of cleanness equipment, drying, classification, storage and industrialization, as well as for the existing equipment adaptation already aiming at to the biggest income and rationalization of energy use. In such a way, this work had as objective to determine some physical properties of grains of organic and conventional coffee. Sphericity and circularity, granular specific mass, porosity and terminal speed had been determined. The work was lead in the laboratories of the UNIOESTE -Cascavel. They had been used supreme of organic and conventional coffee (Coffea arabica, L.) in the stadium coconut, gotten next to the Emater. From the gotten results, it can be concluded that the measure of the ortogonals axles did not present significant difference, when comparative the varieties and the types of treatments. Fruits of coffee in the types organic and conventional and the variety, had not presented difference in the circularity determination. The found values of apparent and real specific mass had been similar to the described ones for other authors, however, comparing the organic coffee with the conventional, it did not have difference of values. The Catuaí variety organic treatment, presented greater average value of porosity, however significant difference between organic and conventional coffee in the two analyzed varieties was not observed. The organic treatments had presented, in the determination of terminal speed, values about 9% superiors to the conventionals